An assessment of integrated watershed management in Ethiopia - Gebregziabher, Gebrehaweria; Abera, D.A.; Gebresamuel, G.; Giordano, Meredith A.; Langan, Simon J. (International Water Management Institute, 2016)
Sustainable participatory watershed management is an approach promoted by the Ethiopian government to restore natural resources and agricultural productivity across the country. This comparative study between six watershed programs shows that this approach increases farmers’ food security and incomes (around 50% on average), as well as their resilience to drought and other climate shocks. However, the study also confirms that the nature and scale of impact can vary significantly between watershed programs. The success of watershed management depends on multiple factors from the hydrological profile of the watershed to the local social and economic environment. Tailoring watershed interventions to the local context, associating conservation and livelihoods activities, and providing further financial and technical support to watershed committees are among the recommendations of this paper.